Hexose transporters of a hemibiotrophic plant pathogen: functional variations and regulatory differences at different stages of infection. - Lingner, Ulrike; Münch, Steffen; Deising, Holger B.; Sauer, Norbert (Journal of Biological Chemistry, 2011)
Plant pathogenic fungi use a wide range of different strategies to gain access to the carbon sources of their host plants. The hemibiotrophic maize pathogen Colletotrichum graminicola (teleomorph Glomerella graminicola) colonizes its host plants, and, after a short biotrophic phase, switches to destructive, necrotrophic development. Here we present the identification of five hexose transporter genes from C. graminicola, CgHXT1 to CgHXT5, the functional characterization of the encoded proteins, and detailed expression studies for these genes during vegetative and pathogenic development. Whereas CgHXT4 is expressed under all conditions analyzed, transcript abundances of CgHXT1 and CgHXT3 are transiently up-regulated during the biotrophic phase, and CgHXT2 and CgHXT5 are expressed exclusively during necrotrophic development. Analyses of the encoded proteins characterized CgHXT5 as a low-affinity/high-capacity hexose transporter with a narrow substrate specificity for glucose and mannose. In contrast, CgHXT1 to CgHXT3 are high affinity/low capacity transporters that also accept other substrates, including fructose, galactose, or xylose. CgHXT4, the largest of the identified proteins, has only little transport activity and may function as a sugar sensor. Phylogenetic studies revealed hexose transporters closely related to the five CgHXT proteins also in other pathogenic fungi suggesting conserved functions of these proteins during fungal pathogenesis.